Zeolite from Zirconium-Modified Fly Ash Waste for Absorption of Phosphate Compounds in Waters - Putri, Mu'izzah Irsyadi; Saefumillah, Asep; Bakri, Ridla (Jurnal Kimia Valensi, 2023)
Eutrophication is a phenomenon of decreasing air quality caused by the very high amount of phosphate ions in the aquatic system. Thus, an effective and efficient adsorbent is needed for phosphate absorption in aquatic systems. In this study, zeolit from fly ash waste was modified with zirconium (Zr) as an adsorbent for phosphate absorption in aquatic systems. Fly ash was pretreated with acid and then synthesised using the hydrothermal method. And then, the results of the fly ash zeolit synthesis were continued using zirconium. The adsorption capacity was tested through several parameters, including the adsorbent concentration test, variations in pH,and contact time. Zirconium-modified zeolite (ZrMZ) adsorbent was the most effective adsorbent for phosphate adsorption, with an adsorption capacity of 3.015 mg-P/g at a 3 g/L adsorbent dosage and pH 7. The adsorption kinetics for the ZrMZ adsorbent followed pseudo-second-order kinetics. The best result of ZrMZ adsorbent to absorb phosphate in lake water was an adsorption capacity value of 0.186 mg-P/g and an adsorption efficiency of 81.137%.